In situ electrochemical high‐energy X‐ray diffraction using a capillary working electrode cell geometry. (26th May 2017) - Young, Matthias J.; Bedford, Nicholas M.; Jiang, Naisheng; Lin, Deqing; Dai, Liming
Abstract : An electrochemical cell design for in situ high‐energy X‐ray diffraction which provides an order of magnitude signal enhancement over traditional cell designs is presented. Various examples illustrate improved diffraction signal and cell operation. Abstract : The ability to generate new electrochemically active materials for energy generation and storage with improved properties will likely be derived from an understanding of atomic‐scale structure/function relationships during electrochemical events. Here, the design and implementation of a new capillary electrochemical cell designed specifically for in situ high‐energy X‐ray diffraction measurements is described. By increasing the amount of electrochemically active material in the X‐ray path while implementing low‐ Z cell materials with anisotropic scattering profiles, an order of magnitude enhancement in diffracted X‐ray signal over traditional cell geometries for multiple electrochemically active materials is demonstrated. This signal improvement is crucial for high‐energy X‐ray diffraction measurements and subsequent Fourier transformation into atomic pair distribution functions for atomic‐scale structural analysis. As an example, clear structural changes in LiCoO2 under reductive and oxidative conditions using the capillary cell are demonstrated, which agree with prior studies. Accurate modeling of the LiCoO2 diffraction data using reverse Monte Carlo simulations further verifies accurate background subtraction and strong signal from the electrochemically active material, enabled by the capillary working electrode geometry.